”Att vara same var att bära sin historia med sig, att stå med den tunga ryggsäcken framför sig som barn och välja att bära den eller inte” : Samisk identitet och koloniala arv i Ann-Helén Laestadius roman Stöld - Kristofersdotter Ekeke, Veronica (Mittuniversitetet, Institutionen för humaniora och samhällsvetenskap, 2022)
Stöld by Ann-Helén Laestadius depicts a small postcolonial society in Northern Sweden, where tension and hate crimes towards the Sami population is part of the norm. This essay analyzes stereotypes, dichotomies, and portrayals of the Sami people as “the other” in Stöld, while discussing Sami identity, colonial heritage, and its effects. The theoretical foundation of the analysis draws from a postcolonial perspective, which points to how Stöld lifts and deconstructs Sami stereotypes, dichotomies, otherification, and colonial ideas, while making Sami perspectives more visible. Slutgiltigt godkännandedatum: 2022-06-01